Traits of Adaptive Outdoor Thermal Comfort in a Tropical Urban Microclimate - Fong, Chng Saun; Manavvi, Suneja; Priya, Radhakrishnan Shanthi; Ramakreshnan, Logaraj; Sulaiman, Nik Meriam; Aghamohammadi, Nasrin (Atmosphere, 2023)
Urban heat islands (UHIs) are negatively impacting the quality of the urban environment and outdoor thermal comfort (OTC) levels, which have raised concerns regarding their impact on urban health and well-being. Understanding of OTC level is crucial, particularly in tropical cities with year-round high temperatures and humidity. A study was conducted in Kuala Lumpur (KL), Malaysia, to determine the OTC level in a selected urban area through microclimate measurements and questionnaire surveys with 1157 respondents. Over half of the urban dwellers reported thermal discomfort, with a high perceived OTC level, indicating strong thermal adaptive behaviours among the urban dwellers despite the physiological stress. Confounding factors such as urban morphology, land cover and human activity patterns also influence the OTC level in the tropical city. The findings emphasize the need for interventions to improve the urban environment and promote better outdoor thermal comfort for city dwellers through measures such as green infrastructure, UHI mitigation and increasing public awareness.